Machine translation and postediting in the didactics of translation and interpreting - González Pastor, Diana (2021)
Introduction: This paper presents the results of an educational experience within the framework of POSEDITrad, an educational innovation project that incorporates the use of machine translation and postediting in the translation classroom within the Degree of Translation and Interlinguistic Mediation at the University of Valencia (Spain). Theoretical framework: Technology and machine translation are envisaged as helpful tools that can enhance both the translation process and the students’ translation competence. Procedure: This curricular innovation includes the design and implementation of a series of activities that provide students with the necessary tools, techniques and procedures in machine translation and post-editing to fulfil translation market demands and foster students’ technological competence. Discussion: The benefits of this teaching innovation are associated with an increase in student’s employability. Similarly, this experiment paves the way for an innovative curriculum design in the field of translation didactics.